Determinants Of Knowledge Management Success In Public Companies In Kenya - Sacho, Zammary Jepkorir; Senaji, Thomas A. (Advances in Social Sciences Research Journal, 2021)
In a knowledge economy, the need to ensure knowledge management success is imperative because it determines the success of an organization. Consequently, in order to improve and sustain their competitive advantage, many companies are also exploring the field of knowledge management. We examined factors that influence knowledge management success, namely organizational culture, knowledge strategy, information technology and leader behavior using a descriptive survey of 216 low, middle and top-level managers from public companies in Kenya based in Nairobi. Primary data was collected using structured questionnaires. The overall response rate was 72 percent. Descriptive statistics were used to summarize the analyzed survey data into frequencies and means. The findings were that organizational culture (β = 0.185, t = 5.436, p < 0.001), knowledge strategy (β = 0.368, t = 9.622, p < 0.001), information technology (β = 0.338, t = 9.247, p < 0.001) and leader behavior (β = 0.187, t = 4.764, p < 0.001) had a positive and significant influence on knowledge management success. Based on these findings, it is recommended that organizations have a knowledge strategy and enhance their information technology because these were found to have the greatest influence on knowledge management success.